MEMBINCANG AGAMA DAN NEGARA TANPA KEKERASAN GENDER - Solihin, SAg.,MH., Nur (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2008)
Violence towards women in Indonesia which is conducted whether by individual, family, society and state (itself) is a continuing phenomenon. Various concepts on this sort of case are offered by experts, seminars, discussions to give solution. Furthermore, CEDAW (Convention on the Elimination of Discrimination Against Women) has been ratified since May, 1982 by Indonesia as legal platform to eliminate the violence. On the contrary, the state involves in several violence cases(particularly in new order era) such as the case in Aceh, East Timor, Irian Jaya and chaos in May, 1998 of which most women are the victims. Domestic violence is another feature of women’s condition under the banner of state ideology and religious ideology that are supported by patriarchal system. This paper points out that democratizing country and reinterpreting religious texts (which are more gender sensitive) are the alternative solutions for aforementioned problems.